2005
DOI: 10.1158/1078-0432.ccr-04-1922
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Lymph Node Metastases in Gastric Cancer Correlates with the Angiotensin I–Converting Enzyme Gene Insertion/Deletion Polymorphism

Abstract: Purpose: In the present study, we aimed to substantiate the putative significance of angiotensin I^converting enzyme (ACE) on gastric cancer biology by investigating the influence of its gene polymorphism on gastric cancer progression. Experimental Design: Genomic DNA was purified from peripheral blood mononuclear cells or tissue specimens. Amplified ACE gene fragments were separated on agarose gels. D or I alleles were identified by the presence of 190-or 490-bp fragments, respectively. Local expression of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 30 publications
3
98
1
4
Order By: Relevance
“…ACE may not affect the incidence of digestive system cancer, however, it may affect the progression of digestive system cancer. Rocken et al have found that the gene polymorphism influence the metastatic behavior of gastric cancer (Rocken et al, 2005).Thus, future studies are warranted to identify the associations between ACE polymorphism and the risk of progression and metastasis of digestive system cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ACE may not affect the incidence of digestive system cancer, however, it may affect the progression of digestive system cancer. Rocken et al have found that the gene polymorphism influence the metastatic behavior of gastric cancer (Rocken et al, 2005).Thus, future studies are warranted to identify the associations between ACE polymorphism and the risk of progression and metastasis of digestive system cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype and allele distributions for each case-control study are shown in Table 2. There were 7 studies of Asians (Goto et al, 2005;Sugimoto et al, 2006;Hou et al, 2010;Hibi et al, 2011;Liu et al, 2011;Ji et al, 2012;Yuan et al, 2013), 8 of Europeans (Ebert et al, 2005;Rocken et al, 2005;Nikiteas et al, 2007;Rocken et al, 2007;van der Knaap et al, 2008;Toma et al, 2009;Kupcinskas et al, 2011;Lukic et al, 2011). In this meta-analysis, the most studied cancers were gastric cancer and colorectal cancer, the genotype methods are a classic PCR assays.…”
Section: Studies Selection and Characteristics In The Meta-analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Angiotensin II (Ang II), the main biologically active peptide of the RAS, is converted from angiotensin I (Ang I) via angiotensin I-converting enzyme (ACE).ACE is differentially expressed in several carcinomas and may affect tumor cell proliferation,migration and angiogenesis (Rocken et al, 2005). The human ACE gene contains many polymorphisms,which is located on chromosome RESEARCH ARTICLE Insertion/deletion (I/D) in the Angiotensin-converting Enzyme Gene and Breast Cancer Risk: Lack of Association in a Metaanalysis Xin-Hong Pei 1,3 , Hui-Xiang Li 2,3 * 17q23, and the 287-bp Alu insertion/deletion (I/D, rs4646994) polymorphism in intron 16 is widely studied (Haiman et al, 2003), and ACE I/D polymorphism has been related to ACE levels (Villard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Röcken et al 76 reported that ACE is expressed locally in gastric cancer and that the ACE gene polymorphism influences metastatic behaviour. Twenty-four of 113 (21%) gastric cancer patients had the II, 57 (51%) the ID, and 32 (28%) the DD genotype.…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%